Sierra Leone Economic Update, June 2018 : Reviving Urban Development - The Importance of Freetown for the National Economy - World Bank Group (World Bank, Freetown, 2018)
The Sierra Leone Economic Update (SLEU) reports on and analyzes recent economic developments and policies within medium-term, regional, and global contexts and analyzes the implications of these developments and policies for the outlook of the economy. Macroeconomic imbalance worsened in 2017 due to high levels of fiscal deficit and rising debts, inflationary pressure, a fragile banking system, and current account pressures. Stabilizing the macroeconomy is precondition for inclusive growth and poverty reduction. Key macroeconomic and sectoral reforms will need to be implemented to reduce the imbalances and to avert downside risks to economic growth. The special topic of this update report is an urban sector review of Sierra Leone's capital, Freetown, with a focus on the city's potential contribution to inclusive national economic growth. It has been demonstrated that cities are the places where significant economic development happens. The importance of Freetown to Sierra Leone's economy is clear, with the city creating 30 percent of the country's GDP despite having only 15 percent of its population. Rapid urbanization is now Sierra Leone's biggest growth narrative for the 21st century. Freetown has the potential to power economic transformation for Sierra Leone by bringing together large numbers of workers and entrepreneurs, and by serving as a hub for large-scale production in services, agro-processing and retail trade to complement and add value to existing production.